Penerapan Prinsip–Prinsip Good Governance dalam Penyelenggaraan Pelayanan Administrasi Terpadu Kecamatan (PATEN) di Kecamatan Curug Kota Serang - Nasyaya, Az Zahra Himayatun; Handayani, Nida (TSAQOFAH, 2026)
This study departs from the importance of applying good governance principles in the provision of public services at the subdistrict level, particularly within the PATEN program in Curug Subdistrict. It aims to analyze the implementation of the principles of transparency, accountability, responsiveness, and participation in the administration of PATEN, using Dwiyanto’s theory as the analytical framework. The study employed a qualitative descriptive method, with data collected through interviews, observations, and documentation. The findings indicate that the implementation of PATEN in Curug Subdistrict has proceeded reasonably well through integrated coordination, a one-stop service system, and the application of standard operating procedures (SOPs) in accordance with existing regulations. Nevertheless, several challenges remain, including limitations in non-ASN human resources, performance reporting that is not yet fully transparent, inadequate facilities and infrastructure, and low levels of community participation in service evaluation. The study concludes that there is a need to enhance staff capacity, strengthen public information systems, improve service facilities, and develop mechanisms for community participation so that good governance principles in the administration of PATEN in Curug Subdistrict can be implemented more optimally.